2010
DOI: 10.5851/kosfa.2010.30.4.597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inclusion of Lacquer (Rhus verniciflua Stokes) Meal on Carcass Traits and Meat Quality in Growing-finishing Pigs

Abstract: In this study, pigs [n=117; (Landrace × Yorkshire) × Duroc; 64±0.5 kg initial body weight] were used to investigate the effect of feeding different levels of lacquer (Rhus verniciflua Stokes) meal on performance, carcass traits and quality of meat kept under refrigeration at 3±1 o C. The pigs were randomly allotted to 3 treatments on the basis of body weight and sex and each treatment was replicated 3 times (13 pigs in each replicate). Lacquer meal in sawdust form obtained from the stem bark and heartwood of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The RV extract is used to treat gastritis and atherosclerosis as oriental medicine [ 5 ], making it potentially useful for domestic animals. It has been reported that dietary RV extract increased fat digestibility in broiler chickens [ 11 ] and improved the oxidative stability of pork meats [ 10 ] without affecting growth performance. In this study, we evaluated the effects of graded levels of RVS on laying performance, egg quality, lipid metabolism and cecal microflora in laying hens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RV extract is used to treat gastritis and atherosclerosis as oriental medicine [ 5 ], making it potentially useful for domestic animals. It has been reported that dietary RV extract increased fat digestibility in broiler chickens [ 11 ] and improved the oxidative stability of pork meats [ 10 ] without affecting growth performance. In this study, we evaluated the effects of graded levels of RVS on laying performance, egg quality, lipid metabolism and cecal microflora in laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, urushiol is an oily organic component and exerts several beneficial effects such as antimicrobial [ 7 ], and antioxidant [ 8 ] activities. Due to the afore-mentioned effects [ 7 , 8 ], RV and urushiol were tested as the feed supplements to enhance health and/or productivity in pigs [ 9 , 10 ] and broiler chickens [ 11 ]. However, it is reported that urushiol might have toxic effects as it is the main antigen of Rhus and exhibits strong antigenicity in animals [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also improved the oxidative stability of meat in finishing pigs but without affecting carcass traits and performance (Song et al, 2008). In another study, it was indicated that the supplementation of RV meal in the diet of growing-finishing pigs improved carcass traits and decreased back fat thickness during refrigerated storage (Song et al, 2010).…”
Section: Introductionmentioning
confidence: 97%